THE INFLUENCE OF EARLY ASSESSMENT IN EARLY CHILDHOOD EDUCATION ON DIFFERENTIAL LEARNING IN AISYIYAH BUSTANUL ATHFAL KINDERGARTEN, MUNTILAN DISTRICT, MAGELANG REGENCY - Solikhah; Agustin Rahayu; Titin Supriatin; Ismiati; Yeni Yuliani Syarif; Brigita Puridawaty (Universitas Panca Sakti Bekasi, 2024)
Every child own stages different developments , potentials , interests and characteristics. One with others, so The role of PAUD teachers is very necessary For develop appropriate and differentiated learning _ for child age early . Learning differentiate in children age early required For develop stages development , potential , as well character participant customized education _ with readiness , interest and style learn it , so required assessment beginning moreover formerly . Study This aim For know influence assessment beginning to learning differentiate . Types of research This is causality with amount respondents as many as 56 people. Statistical tests and data processing are used is Partials Least Square ( SmartPLS 3.0). Research result show that assessment beginning own influence significant direct _ to learning differentiate of 0.618 or 61.8%.